Self-Cleaning Cement Material with Bismuth Titanate Photocatalytic Additive - Kozlova, Irina; Dudareva, Marina; Zemskova, Olga; Korshunov, Andrey; Samchenko, Svetlana (Civil Engineering Journal, 2025)
Nowadays, mortars are building materials with various properties that can be achieved through the careful selection of components and the introduction of different modifying additives. An additive based on the TiO₂–Bi₂O₃ oxide system can be considered a modifying component with photocatalytic and biocidal properties capable of decomposing organic pollutants, viruses, bacteria, and fungal spores. The purpose of the work was to obtain cement compositions containing the additive, study their physical and mechanical properties, evaluate their photocatalytic activity in accordance with the UNI 11259-2016 standard, and assess their resistance to mold fouling. In this study, samples of cement–sand plaster with the TiO₂–Bi₂O₃ additive synthesized via citrate-based technology at 1.7 and 5.0 wt.% were prepared, and their physical, mechanical, photocatalytic, and biocidal properties were examined. As a result, the authors identified photocatalytic activity in both the UV and visible spectra, achieving 69% after 26 hours of UV irradiation. The samples demonstrated 100% resistance to mold fouling. The compressive strength of the modified samples increased by 32.0–39.0%; bending strength by 33–38.0%; and adhesion strength to the base by 60–70%. The cost calculation also confirmed the feasibility of introducing the additive at 1.7 wt.% into the cement composition. The resulting cement material formula can be recommended for designing fungi-resistant, self-cleaning plasters.